Notes on Terrible Educations: Auto/Ethnography as Intervention to How we See Black. (July 2019) - Hill, Dominique C.; Callier, Durell M.; Waters, Hill L.
"Notes on Terrible Educations" is a collective auto/ethnographic account of educational experiences. Through the usage of poetry and narrative, storytelling, and fictionalized accounts, this essay interrogates the authors' educational experiences to bare witness, confront, reimagine, and provide redress, as necessary, to those negative experiences, persons, and teachers who shaped their schooling/educational journey.